Digitalisasi Sistem Absensi Real-Time Berbasis QR Code Dengan Validasi Lokasi Untuk Meningkatkan Akuntabilitas Kehadiran Personel - Pamungkas, Bayu; Iswahyudi, Raden Teddy; Anwar, Nizirwan; Ariessanti, Hani Dewi (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2026)
Digital transformation has encouraged organisations to adopt information systems that are more efficient, accurate, and transparent, including in the management of personnel attendance. Conventional manual attendance systems still present significant limitations, such as high susceptibility to human error, data duplication, manipulation, and inefficiency in data processing and reporting. This study aims to design and develop a QR code–based attendance system as a digital solution to improve the reliability and accountability of attendance records. The software development process follows the Waterfall methodology, encompassing requirement analysis, system design, implementation, and testing stages. System modelling is conducted using unified modeling language (UML) diagrams and an entity relationship diagram (ERD) to clearly define system structure and operational workflows. The implemented system enables attendance recording through QR code scanning integrated with a centralised database in real-time, supported by QR validity checks, location validation based on location name or GPS radius, prevention of duplicate scans within a five-minute interval, and automatic determination of attendance status as PRESENT or LATE. System testing is performed using the Black Box Testing method to verify functional compliance from the user’s perspective without examining internal code structures. The testing results demonstrate that all core system functions operate in accordance with the specified requirements and business rules, responding appropriately to both valid and invalid input scenarios. Furthermore, each successful transaction consistently generates attendance records and activity logs, ensuring data integrity, traceability, and accountability. Overall, the proposed QR code–based attendance system effectively enhances efficiency, accuracy, and transparency in attendance management and is considered suitable for operational implementation and further development.